2018
DOI: 10.1002/hbm.24279
|View full text |Cite
|
Sign up to set email alerts
|

White matter microstructure in anorexia nervosa

Abstract: The neurobiological underpinnings of anorexia nervosa (AN) are unclear. White matter deficits have been described in the illness, but findings are inconsistent between studies. The aim of this study was to investigate differences in white matter microstructure in AN using diffusion-weighted imaging (DWI). It was hypothesised that people with AN, relative to a healthy control (HC) group, would show decreased functional anisotropy (FA) and increased mean diffusivity (MD) in the fornix and superior longitudinal f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 42 publications
(79 reference statements)
1
17
1
Order By: Relevance
“…Indeed, a recent study on the general population showed that malnutrition was mostly linked with a reduction in FA and with changes in neuropsychological results (Roy et al, 2015). Barona et al (2019) found an increased FA in different areas but this difference could be explained by the preliminary characteristic of meta-analysis studies of DWI in AN, as well as by the methodology applied: indeed, they included studies with acute patients without a full diagnosis of AN (Olivo et al, 2017) or without whole brain foci results (Cha et al, 2016), whereas our meta-analysis includes a higher number of studies (such as Phillipou, Carruthers, et al, 2018;Miles et al, 2018;and unpublished data;von Schwanenflug et al, 2019).…”
Section: /9mentioning
confidence: 95%
See 3 more Smart Citations
“…Indeed, a recent study on the general population showed that malnutrition was mostly linked with a reduction in FA and with changes in neuropsychological results (Roy et al, 2015). Barona et al (2019) found an increased FA in different areas but this difference could be explained by the preliminary characteristic of meta-analysis studies of DWI in AN, as well as by the methodology applied: indeed, they included studies with acute patients without a full diagnosis of AN (Olivo et al, 2017) or without whole brain foci results (Cha et al, 2016), whereas our meta-analysis includes a higher number of studies (such as Phillipou, Carruthers, et al, 2018;Miles et al, 2018;and unpublished data;von Schwanenflug et al, 2019).…”
Section: /9mentioning
confidence: 95%
“…Five articles out of 18 reported an increased FA in AN patients compared to HC, with modifications in different brain areas (Cha et al, 2016;Frank, Shott, Hagman, & Yang, 2013;Hayes et al, 2015;Travis et al, 2015;Vogel et al, 2016). Fourteen studies out of 17 reported a reduced FA in AN patients (Cha et al, 2016;Frank et al, 2013;Frank, Shott, Riederer, & Pryor, 2016;Frieling et al, 2012;Gaudio et al, 2017;Hayes et al, 2015;Hu et al, 2017;Kaufmann et al, 2017;Kazlouski et al, 2011;Nagahara et al, 2014;Phillipou, Carruthers, et al, 2018;Travis et al, 2015;Via et al, 2014;von Schwanenflug et al, 2019). The area of reduced FA seems to spread to different brain areas.…”
Section: Systematic Reviewmentioning
confidence: 98%
See 2 more Smart Citations
“…Unfortunately, their results are not consistent. Most studies report lower FA in widespread WM regions, including the corpus callosum (CC) (Frieling et al, 2012;Frank et al, 2013;Shott et al, 2016;Gaudio et al, 2017;Phillipou et al, 2018;von Schwanenflug et al, 2019), fornix fibers (Kazlouski et al, 2011;Frank et al, 2013;Gaudio et al, 2017), thalamus (Frieling et al, 2012;Hu et al, 2017), cingulum (Kazlouski et al, 2011;Frank et al, 2013), posterior thalamic radiation (PTR) (Phillipou et al, 2018), superior longitudinal fasciculus (SLF) (Via et al, 2014), fronto-occipital fasciculus (FOF) (Kazlouski et al, 2011;Via et al, 2014), corona radiation (Shott et al, 2016;Phillipou et al, 2018) and cerebellum (Nagahara et al, 2014;Shott et al, 2016). Five studies, however, observed no significant FA differences between AN patients and HC (Yau et al, 2013;Cha et al, 2016;Pfuhl et al, 2016;Bang et al, 2018;Olivo and Swenne, 2019).…”
Section: Introductionmentioning
confidence: 99%